The effectiveness and safety of continuous and repeated treatment of atosiban in twin pregnancy with threatened preterm labor: A propensity score-matched study. - Hao Zhu; Weirong Gu; Bian Wang; Rong Hu (PLoS ONE, 2025)
Purpose This retrospective cohort study aimed to evaluate the effects and adverse outcomes of continuous and repeated treatment with atosiban in twin pregnancies with threatened preterm labor. Patients and methods The study was conducted at the Department of Obstetrics, Obstetrics and Gynecology, Hospital of Fudan University and included 90 twin pregnancies diagnosed with threatened preterm labor between January 2018 and December 2022. The pregnancies received atosiban tocolytic treatment. The data was divided into two groups based on whether continuous and repeated treatment was administered. Delivery outcomes, as well as maternal and neonatal complications, were analyzed. Propensity score matching (PSM) was employed to create comparable groups. Results Out of the 90 women, 34 received continuous and repeated treatment, while 56 did not. After PSM, 33 women who received continuous and repeated treatment were matched with 33 women who did not. The continuous and repeated treatment group showed a significant prolongation of pregnancy (p = 0.001) with a hazard ratio of 0.58 (95%CI, 0.35-0.96), and a later gestational age (p = 0.042). These patients also had a more complete cycle of antenatal steroids (p = 0.002) and a lower proportion of cases requiring operative delivery due to fetal distress (OR=0.14 [0.03-0.75], p = 0.004). Additionally, neonates in the continuous and repeated treatment group had a lower rate of admission to the neonatal intensive care unit (NICU) (OR=0.41 [0.19-0.89], p = 0.023). Conclusion This propensity score-matched study suggests that continuous and repeated treatment with atosiban may effectively prolong pregnancy in cases of twin pregnancies with threatened preterm labor. Continuous and repeated treatment with atosiban was associated with lower fetal distress and lower NICU admission but no effect in adverse neonatal outcomes as well as the incidence of chorioamnionitis.